The Potential of Asian Swamp Eel (Monopterus Albus) as A Functional Food for Anemia: A Scoping Review - Iis Sulastri; Wachid Putranto; Lilik Wijayanti (Indonesian Journal of Global Health Research, 2025)
Anemia remains a significant global health issue. One of the causes is the inadequate of protein and iron intake. So that, erythropoiesis in body less than optimal. Asian swamp eel (Monopterus albus) can potentially be a functional food that can be included food products because it is rich in nutriens that have a potential impact on anemia. Objective: This scoping review aim was to explores the nutritional composition of Asian swamp eel and its effects on anemia, focusing on mechanisms by which its nutrients influence anemia biomarkers. Methods: This scoping review was performed using the 5-step Arkeys and O’Malelev framework and reported according to PRISMA ScR. Two electronic databases were searched systematically. Article are included if eligible. Results: The result was descriptive and qualitative analyses. A total of 1,245 articles were collected. Key findings suggest that the high protein and vitamin content in eel can significantly improve hemoglobin levels and other anemia indicators. Conclusions: This review highlights the potential of incorporating eel into dietary interventions as a sustainable and effective approach to mitigating anemia prevalence.